Generalized Gaussian Quadrature Formulas with Chebyshev Nodes (Journal of Computational Mathematics, 1999)
Explicit expressions of the Cotes numbers of the generalized Gaussian quadrature formulas for the Chebyshev nodes (of the first kind and the second kind) and their asymptotic behavior are given. \u00a0